Bringing the Children’s Songs of the Rungus of Sabah into Malaysian Music Classrooms - Jinky Jane C. Simeon; Jacqueline Pugh-Kitingan (UPSI Press, 2021)
The Rungus are one of the indigenous Dusunic ethnic groups of Sabah, most of whom reside in the administrative Districts of Kudat and Pitas. In Rungus culture, many different genres of intangible cultural heritage have been passed down orally over generations. These heritages are valuable resources for teaching cultural awareness and appreciation among children of different ethnicities in Malaysia. They have yet to be introduced in the national music education curriculum. The purpose of this research was to document, transcribe, analyse, and thereafter to select the appropriate longoi tanganak (children’s songs) and longoi pogondoi (lullabies) that are suitable to be introduced into the Malaysia primary school music curriculum based on the recommendations of the culture bearers. This research employed ethnographic field techniques including participant observations, in-depth and focus group interviews, as well as audio and video recording. This article taps on the suggestions of culture bearers in developing suitable song repertoires that serve as school music teachers’ resources. Findings show that culture bearers recommended counting songs performed in recited heighten speech, songs arranged in the do- re- mi- so and do- mi- so tone sets, and rhythmic motifs based on the and patterns as beginner repertoire for learning Rungus songs.